Analisis Key Performance Indikator (Studi Kasus pada PT. Asgility) - Firstson Siom (Majalah Ilmiah Bahari Jogja, 2020)
The aim study is to analyze the effect of delivery orders, custom clearance, and delivery on key performance indicators (KPI), using the correlational method at PT. Agility as freight forwarding. Data collection by survey. The result that issuance of delivery orders has no effect on delivery, custom clearance has a direct effect on delivery, issuance of delivery orders has a direct effect on KPI achievement, custom clearance has a direct effect on KPI achievement, and finally delivery has a direct effect on KPI achievement.